Sustainable evaluation of ecotourism in the Yangtze River delta urban agglomeration: A system coordination perspective - Jiqiang Zhao; Jian Pan; Ling Tan (Sustainable Operations and Computers)
The coordinated development of the ecosystem (ES) and the tourism system (TS) is crucial for the sustainable ecotourism of urban agglomerations. From the perspective of the coordinated sustainable development of the ecotourism system (ETS), this study introduces a novel approach to evaluate the sustainable ecotourism performance of urban agglomeration in the Yangtze River Delta (YRDUA). By employing network the slack-based measure (SBM) and coordination coupling degree (CCD) models, using the support vector machine recursive feature elimination (SVM-RFE) method, the study identifies the efficiency of the ETS, the coordination between ES and TS, as well as key factors affecting the sustainability of ecotourism. The findings reveal an annual increase in the coordination between the ES and TS, although COVID-19 has significantly impacted their coupling and efficiency. Despite this, the efficiency of the ES has remained relatively stable. It is worth noting that the transportation sector and the tertiary industry have become core drivers of ETS sustainable development, with contribution a rate of 39.5 % and 27.05 % respectively.